Literature Riview: Peran Teknologi Informasi dalam Meningkatkan Efisiensi dan Efektivitas Birokrasi - Dede Mirza; Lili Suryani; Latip Latip; Variza Aditiya (LPPM STIA Lancang Kuning Dumai, 2023)
Information technology plays a crucial role in improving the efficiency and effectiveness of bureaucracy. One of the benefits of information technology is speeding up access to organizational processes, allowing for faster and more accurate decision-making. Moreover, information technology can improve the efficiency, productivity, and effectiveness of employees and companies, as well as enhance public services. The application of information technology in bureaucracy can also help improve public services and efficiency. The development of digital bureaucracy is also one of the efforts to improve the efficiency and effectiveness of bureaucracy. In existing literature, information technology has an important role in enhancing the efficiency and complexity of bureaucracy. The research method used is a literature study with various research journals and an analytical research design supported by data on the Role of Information Technology in Improving the Efficiency and Effectiveness of Bureaucracy.